Emerging functions of pannexin 1 in the eye - Kurtenbach, Sarah; Kurtenbach, Stefan; Zoidl, Georg (Frontiers in Cellular Neuroscience, 2014)
Pannexin 1 (Panx1) is a high-conductance, voltage-gated channel protein found in vertebrates. Panx1 is widely expressed in many organs and tissues, including sensory systems. In the eye, Panx1 is expressed in major divisions including the retina, lens and cornea. Panx1 is found in different neuronal and non-neuronal cell types. The channel is mechanosensitive and responds to changes in extracellular ATP, intracellular calcium, pH, or ROS/nitric oxide. Since Panx1 channels operate at the crossroad of major signaling pathways, physiological functions in important autocrine and paracrine feedback signaling mechanisms were hypothesized. This review starts with describing in depth the initial Panx1 expression and localization studies fostering functional studies that uncovered distinct roles in processing visual information in subsets of neurons in the rodent and fish retina. Panx1 is expressed along the entire anatomical axis from optical nerve to retina and cornea in glia, epithelial and endothelial cells as well as in neurons. The expression and diverse localizations throughout the eye points towards versatile functions of Panx1 in neuronal and non-neuronal cells, implicating Panx1 in the crosstalk between immune and neural cells, pressure related pathological conditions like glaucoma, wound repair or neuronal cell death caused by ischemia. Summarizing the literature on Panx1 in the eye highlights the diversity of emerging Panx1 channel functions in health and disease.